2022
DOI: 10.1021/acscatal.2c04863
|View full text |Cite
|
Sign up to set email alerts
|

Designing Reactive Bridging O2– at the Atomic Cu–O–Fe Site for Selective NH3 Oxidation

Abstract: Surface oxidation chemistry involves the formation and breaking of metal−oxygen (M−O) bonds. Ideally, the M−O bonding strength determines the rate of oxygen absorption and dissociation. Here, we design reactive bridging O 2− species within the atomic Cu−O−Fe site to accelerate such oxidation chemistry. Using in situ X-ray absorption spectroscopy at the O K-edge and density functional theory calculations, it is found that such bridging O 2− has a lower antibonding orbital energy and thus weaker Cu− O/Fe−O stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…In the i-SCR mechanism, nitrates, such as bidentate and monodentate nitrates, were regarded as major intermediates. 19,20,54,55 Herein, a hyponitrite ion (N 2 O 2 2− ) was observed over CuO x /PtCu catalysts by in situ DRIFTS, in good agreement with the bands observed by Liu et al 20 A reaction path named the O lat assisted i-SCR mechanism was then proposed by combining DFT calculations and in situ DRIFTS. First, NH 3 dehydrogenation is assisted by O lat and active O simultaneously.…”
Section: Structure and Chemical State Characterization Ofsupporting
confidence: 83%
See 2 more Smart Citations
“…In the i-SCR mechanism, nitrates, such as bidentate and monodentate nitrates, were regarded as major intermediates. 19,20,54,55 Herein, a hyponitrite ion (N 2 O 2 2− ) was observed over CuO x /PtCu catalysts by in situ DRIFTS, in good agreement with the bands observed by Liu et al 20 A reaction path named the O lat assisted i-SCR mechanism was then proposed by combining DFT calculations and in situ DRIFTS. First, NH 3 dehydrogenation is assisted by O lat and active O simultaneously.…”
Section: Structure and Chemical State Characterization Ofsupporting
confidence: 83%
“…The major difference between the TPSR process and NH 3 -SCO reaction was that O lat consumed by pre-absorbed ammonia could be replenished by oxygen rapidly during the NH 3 -SCO process. Thus, it was reasonable to speculate that O v generated from the O lat assisted NH 3 dehydrogenation process was beneficial to N 2 selectivity. ,,, In Figure S19, DFT calculations confirmed that O lat (lattice O) or O lat H in CuO x dominates the NH 3 dehydrogenation and activation rather than O* (active oxygen). The energy barrier of O lat * assisted NH 3 dehydrogenation was observed to be lower than O lat H*, which suggests that O lat H* assisted ammonia dehydrogenation has little tendency to occur.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Density functional theory (DFT) calculations support this hypothesis, showing the weakened O–O bond and the increased bond length of the oxygen molecule on the Co 3 O 4 (100) surface (Figure a) with an adsorption energy of −5.27 eV (Table S1). In comparison, the calculated results over the CuO (001) surface show physical O 2 adsorption with −0.13 eV adsorption energy …”
Section: Resultsmentioning
confidence: 92%
“…In comparison, the calculated results over the CuO (001) surface show physical O 2 adsorption with −0.13 eV adsorption energy. 45 Such an O 2 activation is observed in the O K edge near edge X-ray absorption fine structure (NEXAFS). After oxygen was introduced, the peak of gaseous oxygen in the O K edge (Figure S1, 530.6 eV) was not observed on the surface of Co 3 O 4 , while a peak at 530.1 eV was observed (Figure 1b).…”
Section: 4mentioning
confidence: 99%